Proses Pembelajaran Seni Tari Melalui Teknik Motivasi DI SMP Negeri 1 Rambutan Banyuasin - Mega Fadillah; Treny Hera; Fadhilah Hidayatullah (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This research aims to find out and describe the dance forms of middle children in the Tuah Merindu art studio, PulauBeringin District, South OKU Regency. The method used in this research is a qualitative descriptive method discussing the dance forms of middle children. This research uses primary data sources and secondary data sources. The data collection techniques used are observation techniques, interview techniques and documentation techniques. The results of this research, the middle child dance was created in 2019 which has the meaning "nak iduptareknyawe" where middle children are required to be tougher and tougher in living life. Over time, this dance is carried out with the aim of preserving and maintaining regional traditional dances that have been passed down from generation to generation so that they are known to the outside community and are not lost over time. The forms in the middle child's dance at the Tuah Merindu art studio, PulauBeringin District, South OKU Regency have elements, namely 1). Theme, 2). Motion, 3). Dancer, 4), Property, 5). Music, 6). Makeup 7). Clothing, 8). Floor Patterns, 9). Expression/Pattern, 10). Storyline, 11). Dramatic Plot, 12). Settings, 13). Stage, 14). Lighting.